Understanding grooming discourse in computer-mediated environments. (June 2016) - Lorenzo-Dus, Nuria; Izura, Cristina; Pérez-Tattam, Rocío
Abstract: Online grooming affects a significant number of children and teenagers. Yet research into its characteristics is scarce. This study uses a Computer-Mediated Discourse Analysis approach (Herring, 2004, 2013 ) in order to examine a corpus of online grooming chat logs (c. 75, 000 words) from Perverted-Justice.com. Results reveal the following idiosyncratic features: (1) a marked used of explicit and direct sexual solicitation; (2) a wide range of deceptive trust development strategies; and (3) an emphasis on testing the victim׳s compliance levels throughout the entire chat log and beyond groomers׳ secrecy and exclusivity establishing concerns. Online grooming is found to operate as a complex interactional network and to encompass different groomer profiles. To accommodate these findings, a new model of online grooming discourse is proposed. Highlights: The article describes the first model of online grooming discourse. The model is based on analysis of a large corpus of online groomer chatlogs, focussing on the groomers' contributions. The findings reveal that online grooming is a complex entrapment network, rather than a linear or cyclical process. Building trust discursively is paramount to groomers' aims in online environment and it is realised via a range of communicative processes and strategies that include testing victims' compliance, desensitising and isolating them. Compliments and small talk are identified as particularly effective means used by online groomers in the corpus for building their victims' trust. Online grooming discourse already providers groomers with sexual gratification.